THE ROLE OF THE APPLICATION OF INNOVATIVE TECHNOLOGIES AND TECHNOLOGIES IN THE TEACHING OF AGRICULTURAL SCIENCES (Universal International Scientific Journal, 2026)
This article will help you understand the use of innovative technologies in education.
Keywords: Education; innovation technology; technologies